Assessment of Poor Home Management Practice of Diarrhea and Associated Factors among Caregivers of Under-Five Years Children in Urban and Rural Residents of Doba Woreda, Ethiopia: Comparative Cross-Sectional Study - Waktole Kebede Fufa; Gebretsadik Berhe Gebremedhin; Gebremedhin Berhe Gebregergs; Taklu Marama Mokonnon (Hindawi Limited, 2019)
Background. Diarrhea is the first cause of illness and the second cause of death in under-five children. Home interventions can prevent 57% of mortality related to diarrhea. However, malpractices were common and the reason for this underutilization was unclear. Thus, this study was aimed at assessing poor home management practice of Diarrhea and associated factors among caregivers of under-five years children in urban and rural residents. Methods. The community-based comparative cross-sectional study was conducted in Doba woreda, Ethiopia, from February 25 to March 15, 2017. Multistage cluster sampling technique was used to study 559 caregivers. An interviewer administered pretested structured questionnaire was used to collect data. Collected data were entered into Epi Info version 3.5.1 and exported to statistical package for social sciences (SPSS) version 20.0 for analysis. The binary logistic regression model was used. In bivariate analysis p-value<0.25 was taken into multivariable analysis. Adjusted odds ratios with their corresponding 95% of CI were used to report results with a significance level of p-value<0.05. Result. 184 urban and 375 rural caregivers were included in the study. Poor home management practice was 55.8% of urban and 85.6% of rural residents. Knowledge level (AOR=2.7(CI[1.3, 6.5]) and AOR=13.4(CI[5.3, 34.0]) and difficulty in preparing oral rehydration salt (AOR=4.0CI[1.4, 11.0]) and AOR=2.4(1.3, 5.3)) were associated factors for both urban and rural residents, respectively. Caregivers of male index child (AOR=2.3(1.2, 4.7)) and age of the caregivers (AOR=0.26(0.09, 0.8)) were associated with poor home practice for urban residents. In rural residents, inaccessibility to zinc supplementation (AOR=2.4(1.2, 5.0)) was among associated factors. Conclusion. Poor home management practice of diarrhea was high in both urban and rural residents. It was higher in rural compared to urban residents. Poor practice was associated with knowledge level, age of the caregivers, sex of the index child, and accessibility of zinc. Health education and community mobilization on home management of diarrhea are important to increase awareness and improve practice level.